Predictors of warfarin‐associated adverse events in hospitalized patients: Opportunities to prevent patient harm. Issue 4 (14th December 2015) - Metersky, Mark L.; Eldridge, Noel; Wang, Yun; Jaser, Lisa; Bona, Robert; Eckenrode, Sheila; Bakullari, Anila; Andrawis, Mary; Classen, David; Krumholz, Harlan M.
Abstract : BACKGROUND: The optimum international normalized ratio (INR) monitoring frequency for hospitalized patients receiving warfarin is unknown. OBJECTIVE: Assess relationship between daily versus less frequent INR monitoring and overanticoagulation and warfarin‐related adverse events. DESIGN: Retrospective cohort study using Medicare Patient Safety Monitoring System data. SETTING: Randomly selected acute care hospitals across the United States. PATIENTS: Patients hospitalized from 2009 to 2013 for pneumonia, acute cardiac disease, or surgery who received warfarin. INTERVENTIONS: None. MEASUREMENTS: (1) Association between frequency of INR monitoring and an INR ≥6.0 or warfarin‐related adverse event. (2) Association between the rate of change of the INR and a subsequent INR ≥5.0 and ≥6.0. RESULTS: Among 8529 patients who received warfarin for ≥3 days, for 1549 (18.2%) the INR was not measured on 2 or more days. These patients had higher propensity‐adjusted odds ratios (ORs) of having a warfarin‐associated adverse event (OR: 1.48, 95% confidence interval [CI]: 1.02‐2.17) for cardiac patients and surgical patients (OR: 1.73, 95% CI: 1.20‐2.48), with no significant association for pneumonia patients. Cardiac and pneumonia patients with 1 day or more without an INR measurement had higher propensity‐adjusted ORs of having an INR ≥6.0 (OR: 1.61, 95% CI: 1.07‐2.41 and OR: 1.92, 95% CI: 1.36‐2.71, respectively). A 1‐day increase in the INR of ≥0.9 occurred in 621 patients (12.5%) and predicted a subsequent INR of ≥6.0 (positive likelihood ratio of 4.2). CONCLUSION: Daily INR measurement and recognition of a rapidly rising INR might decrease the frequency of warfarin‐associated adverse events in hospitalized patients. Journal of Hospital Medicine 2016;11:276–282. © 2015 Society of Hospital Medicine